Some notes on the "pantun" storytelling of the Baduy minority group its written and audiovisual documentation - van Zanten, Wim (Wacana, Journal of the Humanities of Indonesia, 2016)
Baduy pantun stories are part of the larger Sundanese oral tradition of pantun storytelling in west Java. The stories recount the deeds of the nobility of such old Sundanese kingdoms as Pajajaran and Galuh. Although the Baduy still recite the pantun stories in their rituals, in the larger cities to the east of the Baduy village Kan k s pantun recitation almost disappeared. On the basis of short periods of fieldwork in and around Kan k s village between 1976 and 2014, in this essay I shall discuss Baduy pantun storytelling. I shall summarize earlier major publications and analyse some performance aspects of two Baduy pantun stories which I recorded. Although I do not concentrate on the text, I do discuss a few cultural issues arising from the texts. Baduy oral literature also includes children's and women's songs, as well as fables and myths of origin (dong ng) which do not involve music. These will not be discussed here.